2019
DOI: 10.1155/2019/5690345
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Resident Progenitor Cells Coexpress Mesenchymal and Myogenic Markers and Are Not Affected by Chronic Heart Failure-Induced Dysregulations

Abstract: Background and Purpose In heart failure (HF), metabolic alterations induce skeletal muscle wasting and decrease of exercise capacity and quality of life. The activation of skeletal muscle regeneration potential is a prospective strategy to reduce muscle wasting; therefore, the aim of this project was to determine if functional properties of skeletal muscle mesenchymal progenitor cells (SM-MPC) were affected by HF-induced functional and metabolic dysregulations. Methods Gastrocnemius muscle biopsy samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
0
13
0
5
Order By: Relevance
“…However, the percentage of human bmMSCs committed to neurogenesis may be limited as only a small proportion (5.9 ± 2.1) of passage 4 bmMSCs expanded in P/ PL were positive for the neural lineage commitment CD56/NCAM phenotypic marker [64,65]. There are conflicting reports on the expression of CD56/NCAM on human bmMSCs with two studies showing that bmMSCs cultured in 10-20% FBS do not express or express very little CD56 [95,96], while another study showed that the fraction of CD56 bright bmMSCs was less than 15% [97]. A study investigating bmMSCs from five healthy females (age 21-31 years old) expanded in human PL and assessed at passages 2 or 3 showed that the proportion of positive cells varied considerably with the percentage of positive cells extending from 23.6 to 88.5% [98].…”
Section: Discussionmentioning
confidence: 99%
“…However, the percentage of human bmMSCs committed to neurogenesis may be limited as only a small proportion (5.9 ± 2.1) of passage 4 bmMSCs expanded in P/ PL were positive for the neural lineage commitment CD56/NCAM phenotypic marker [64,65]. There are conflicting reports on the expression of CD56/NCAM on human bmMSCs with two studies showing that bmMSCs cultured in 10-20% FBS do not express or express very little CD56 [95,96], while another study showed that the fraction of CD56 bright bmMSCs was less than 15% [97]. A study investigating bmMSCs from five healthy females (age 21-31 years old) expanded in human PL and assessed at passages 2 or 3 showed that the proportion of positive cells varied considerably with the percentage of positive cells extending from 23.6 to 88.5% [98].…”
Section: Discussionmentioning
confidence: 99%
“…Обычно спортивные тренировки стимулируют увеличение массы скелетной мускулатуры за счет активации сателлитных клеток и реализации их потенциала миогенной дифференцировки. Недавно мы показали, что в мышечной ткани пациентов с ХСН хронически активирована программа регенерации мышечной ткани, которая не завершается формированием "взрослой", функциональной мышеч ной ткани; такое состояние является патологическим и было описано ранее для разных типов мышечных дистрофий [3]. Однако в стандартизированных условиях in vitro резидентные стволовые клетки (СК) скелетной мускулатуры пациентов с ХСН активно диф-ференцировались в миотрубки, демонстрируя со храннось регенеративного потенциала мышечной ткани при ХСН [3].…”
Section: Transcriptome Analysis Of Skeletal Muscles Revealed the Effeunclassified
“…Недавно мы показали, что в мышечной ткани пациентов с ХСН хронически активирована программа регенерации мышечной ткани, которая не завершается формированием "взрослой", функциональной мышеч ной ткани; такое состояние является патологическим и было описано ранее для разных типов мышечных дистрофий [3]. Однако в стандартизированных условиях in vitro резидентные стволовые клетки (СК) скелетной мускулатуры пациентов с ХСН активно диф-ференцировались в миотрубки, демонстрируя со храннось регенеративного потенциала мышечной ткани при ХСН [3]. Таким образом, мы пришли к заключению, что активация резидентной СК у пациентов с ХСН возможна, и правильно подобранная программа физической реабилитации может способствовать активации регенераторного потенциала СК скелетной мускулатуры, восстановлению мышечной ткани и росту, препятствовать развитию саркопении и увеличивать толерантность к физическим нагрузкам.…”
Section: Transcriptome Analysis Of Skeletal Muscles Revealed the Effeunclassified
See 2 more Smart Citations